2005
DOI: 10.1177/019027250506800406
|View full text |Cite
|
Sign up to set email alerts
|

Contact in Context: An Examination of Social Settings on Whites' Attitudes Toward Interracial Marriage

Abstract: Using data from a New York Times poll conducted in 2000, we analyze whites' approval of interracial marriage by examining the contexts in which whites have contact with blacks. The contexts can be ordered by the type of contact they provide, from close and personal to distant or hierarchical. The results of our analysis show that the type of contact engendered by a variety of contexts is important in determining attitudes toward interracial marriage. The contacts in most of the social settings are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 33 publications
5
90
0
4
Order By: Relevance
“…Those who have more positive contacts are less likely to discriminate. This is in line with previous studies showing that high-quality contact experiences reduce negative intergroup attitudes (e.g., Johnson and Jacobson 2005;Levin et al 2003;Paolini et al 2004). These results lend partial support to Contact Theory and in particular to scholars arguing that we need to take into account the types of intergroup contacts that people have in order to 20 Additional analyses were conducted to verify if difficulties associated with estimating interaction effects in logistic regressions (such as described in Norton et al 2004) may have affected our conclusions.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Those who have more positive contacts are less likely to discriminate. This is in line with previous studies showing that high-quality contact experiences reduce negative intergroup attitudes (e.g., Johnson and Jacobson 2005;Levin et al 2003;Paolini et al 2004). These results lend partial support to Contact Theory and in particular to scholars arguing that we need to take into account the types of intergroup contacts that people have in order to 20 Additional analyses were conducted to verify if difficulties associated with estimating interaction effects in logistic regressions (such as described in Norton et al 2004) may have affected our conclusions.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…Previous research demonstrated that positive intergroup contacts reduce intergroup attitudes, whereas negative contact tends to increase such negative attitudes. Also, it underlined the particular importance of cross-group friendships in promoting more positive intergroup relations (Johnson and Jacobson 2005;Levin et al 2003;Paolini et al 2004;Pettigrew and Tropp 2006). Based on these considerations, we predict that individuals who have more positive interethnic contact experiences are less likely to discriminate.…”
Section: Interethnic Contactmentioning
confidence: 89%
“…Logistic regression model eliminates respondents who have not given answers to all the variables that are analyzed in the model; therefore the number of individuals analyzed varies according to the questions. As Johnson and Jacobson's study (Johnson and Jacobson 2005) which examines whites' social settings of contact and attitudes towards interracial marriage, age, sex, education, region and amount of contact are analyzed in the logistic regression analysis with the outcome variable of positive/negative attitudes. Survey responses are divided into to two categories, agree (coded 1) and disagree (coded 0).…”
Section: Discussionmentioning
confidence: 99%
“…However, the picture seems to be different when it comes to attitudes towards interracial marriages. Several prior studies in the U.S. that examine attitudes specifically towards interracial marriage among whites show that gender does not affect attitudes towards interracial marriage (Johnson and Jacobson 2005;Hughes and Tuch 2003;Wilson and Jacobson 1995), while other studies show that men are more willing to interracially date than women (Yancey 2009;Yancey 2002;Gardyn 2002;Todd et al 1992). Moreover Mills and Daly's study shows that female respondents reports more negative prejudicial attitudes towards interracial relationships than male respondents (Mills and Daly 1995).…”
Section: Graph 1 Comparison Between the Respondents And The Originalmentioning
confidence: 95%
See 1 more Smart Citation